2020
DOI: 10.22452/iojel.vol3no1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of School Administrative Support and Primary School Teachers’ ICT Literacy to Integrate ICT into the Classrooms in Pahang, Malaysia

Abstract: This study aimed to look at the role of information and communications technology (ICT) literacy of teachers as a mediator between the school administrative support and ICT competence of primary school teachers in Pahang. The researchers developed a mediation model based on relevant literature reviews and subsequently tested the model. This study used a total survey design. The researchers employed stratified cluster sampling to select the pilot study and the actual study samples randomly. A total of 514 teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Unlike Factor A, pre-service teachers in this cluster also care about school support and budget, among the factors that positively affect technology integration. In the literature, it has been found that administrative support has indirect and direct effects on teachers' competencies (Baharuldin et al, 2019). Similarly, according to the pre-service teachers in factor B, the most important obstacle is that teachers are not supported with professional development opportunities in technology integration.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Factor A, pre-service teachers in this cluster also care about school support and budget, among the factors that positively affect technology integration. In the literature, it has been found that administrative support has indirect and direct effects on teachers' competencies (Baharuldin et al, 2019). Similarly, according to the pre-service teachers in factor B, the most important obstacle is that teachers are not supported with professional development opportunities in technology integration.…”
Section: Discussionmentioning
confidence: 99%
“…The current application of technology in education system is a must for every school in every country, as it enables educators and students to engage and communicate with each other directly or indirectly within a learning environment (Bagde et al, 2021;Baharuldin et al, 2019). Technologies that have developed today allow the creation of flexible learning conditions and environments.…”
Section: Efforts To Improve Students' Skills Through Ict-based Educat...mentioning
confidence: 99%
“…Technologies that have developed today allow the creation of flexible learning conditions and environments. Therefore, teachers have challenges that must be answered immediately, i.e., managing and optimizing ICT in learning activities (Baharuldin et al, 2019). As an educator, it is inevitable that one must adjust and be receptive to the evolving needs of students and advancements in technology (Chisango et al, 2020).…”
Section: Efforts To Improve Students' Skills Through Ict-based Educat...mentioning
confidence: 99%
“…The current guidelines for the utilisation of AI-driven technologies, including ChatGPT, have primarily been disseminated within university settings, which overlooks the valuable opportunity for schools to harness the full potential of this technology. Additionally, unresolved issues such as data privacy concerns (Weatherbed, 2023) and the readiness of teachers to effectively harness the potential of ChatGPT also warrant further investigation (Baharuldin et al, 2020). Emerging challenges and developments associated with ChatGPT implementation in education include the need to address potential misuse among pupils, ensuring that its use aligns with ethical practices (Jafar, 2023).…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%